New limits on double electron capture of 40Ca and 180W. (18th August 2016) - Angloher, G; Bauer, M; Bauer, P; Bavykina, I; Bento, A; Bucci, C; Canonica, L; Ciemniak, C; Defay, X; Deuter, G; Erb, A; Feilitzsch, F v; et al.
Abstract: We analyzed low-background data from the CRESST-II experiment with a total net exposure of 730 kg days to extract limits on double electron capture processes. We established new limits for 40 Ca with T 1 / 2 2 ν 2 K > 9.9 × 10 21 y and T 1 / 2 0 ν 2 EC > 1.4 × 10 22 y and for 180 W with T 1 / 2 2 ν 2 K > 3.1 × 10 19 y and T 1 / 2 0 ν 2 EC > 9.4 × 10 18 y at 90% CL. Depending on the process, these values improve the currently best limits by a factor of ∼ 1.4 – 30 .